Process matters: petitions systems in Britain's legislatures. Issue 3 (2nd July 2016) - Bochel, Catherine
ABSTRACT: Over the past 15 years petitions systems have become embedded in the Scottish Parliament and the National Assembly for Wales, and more recently the House of Commons. This article uses the concept of procedural justice, with its emphasis on the fairness of the process by which decisions are made, as an analytical tool to explore four case studies of petitions systems in British legislatures, considering, in particular, the extent to which they enable voice, decision-making and transparency. It illustrates that the application of ideas of procedural justice not only provides us with a useful tool for analysing petitions systems in representative political institutions, but also potentially provides a framework of ideas from which petitions systems, and perhaps other participatory initiatives, may learn.